Effect of sea buckthorn extract on production performance, serum biochemical indexes, egg quality, and cholesterol deposition of laying ducks - Yao, Bing-nong; Liao, Fu-you; Yang, Jiao-yi; Liu, Ai; Wang, Jiao; Zhu, Bao-guo; Feng, Gang; Yang, Sheng-lin (Frontiers in Veterinary Science, 2023)
The purpose of this experiment was to study the effect of sea buckthorn extract (SBE) supplementation on the production performance, serum biochemical indexes, egg quality, and cholesterol deposition of laying ducks. A total of 240 23-week-old laying ducks (female ducks) with similar body weight were randomly divided into four treatment groups with 6 replicates of 10 each. The experimental groups were fed diets supplemented with 0, 0.5, 1.0, and 1.5 g/kg of SBE, respectively. The results showed that the addition of 1.0 g/kg SBE to the diet had significant increase (P < 0.05) in average egg weight and feed conversion ratio. The inclusion of SBE showed the significant improvement (P < 0.05) in yolk weight, shell strength, egg white height and haugh unit. Ducks fed with 1.0 and 1.5 g/kg SBE displayed a significant decrease (P < 0.05) in yolk cholesterol. The significant improvements were observed in the contents of total amino acid essential amino acids, non-essential amino acids, umami amino acids, monounsaturated fatty acids, and docosahexenoic acids of eggs (P < 0.05) when supplemented with SBE. However, the contents of total saturated fatty acids, polyunsaturated fatty acids, n-3 polyunsaturated fatty acids and n-6 polyunsaturated fatty acids in eggs showed decrease when ducks fed with SBE diets (P < 0.05). SBE diets may reduce (P < 0.05) the levels of serum total cholesterol, triglyceride, and low-density lipoprotein cholesterol, while increased (P < 0.05) the levels of serum superoxide dismutase, total antioxidant capacity, and glutathione catalase compared to the control. The levels of serum immunoglobulin G, immunoglobulin A and immunoglobulin M were improved in SBE diets (P < 0.05) in comparation to the control. The addition of SBE to diets can improve feed nutrient utilization, increase egg weight, optimaze egg quality and amino acid content in eggs, reduce blood lipids, improve fatty acid profile and yolk cholesterol in eggs, and increase antioxidant capacity and immunity in laying ducks.